Numerical algorithms for reflected anticipated backward stochastic differential equations with two obstacles and default risk - Jingnan Wang; Ralf Korn (Risks, 2020)
We study numerical algorithms for reflected anticipated backward stochastic differential equations (RABSDEs) driven by a Brownian motion and a mutually independent martingale in a defaultable setting. The generator of a RABSDE includes the present and future values of the solution. We introduce two main algorithms, a discrete penalization scheme and a discrete reflected scheme basing on a random walk approximation of the Brownian motion as well as a discrete approximation of the default martingale, and we study these two methods in both the implicit and explicit versions respectively. We give the convergence results of the algorithms, provide a numerical example and an application in American game options in order to illustrate the performance of the algorithms.
Keywords: 330; numerical algorithm; reflected anticipated backward stochastic differential equations; discrete penalization scheme; discrete reflected scheme